DAMPAK PENCEMARAN LINGKUNGAN TERHADAP KESEHATAN MASYARAKAT PESISIR - Ismi Khoiriyah Maha; Susilawati (CV. ADIBA AISHA AMIRA, 2024)
The environmental and health impacts of large-scale chemical dumping and the resulting pollution have received increasing public attention. Unintentional exposure to various pollutants, such as heavy metals, air pollutants and organic chemicals, can cause various deleterious effects on the human body, resulting in the occurrence and development of various diseases. The dangers of pollution to human health, until now, remain an unresolved dilemma because of the ever-changing complexity of environmental challenges. Therefore, the purpose of compiling this literature review is to add to our insight and find out more about the impact of environmental pollution on the health of coastal communities. This research is a literature review. The writings sought and used in this writing are articles published starting from 2021 to 2023 from various journal sources, both national and international, by analyzing originating from 10 journals so that the results obtained. The level of environmental pollution will determine quality and expectations. live more than ever in the coming decades, especially in some of the less developed areas of the world. So we have to keep our environment in order to remain a healthy environment.